Is UK Risky Money Weakly Separable? A Stochastic Approach - Jane Binner; Thomas Elger; Philipe de Peretti (Lund University, School of Economics and Management, Department of Economics, 2002)
Using non-parametric weak separability tests that are extended to allow for measurement errors in the data, a broad group of UK monetary assets is found to be weakly separable from consumer goods and leisure over the larger part of the nineties. Financial innovations have made assets with substantial interest rate risk (e.g. unit trusts) more liquid and recent developments in monetary aggregation theory dealt with risk and risk aversion in the calculation of user costs. It is, however, not possible to find any weakly separable group of assets that contains 'risky' assets in the current sample.
Keywords: C43; D11; D12; E41; 330; Monetary Aggregation; Weak Separability; Risk